(untitled) (Global Journal of Management and Business Research, 2019)
This paper examines the farmer’s monthly per capita consumption expenditure of food and nonfood items in the dry region of western Maharashtra using the field survey data 2015-16. The present study was carried out in eighteen villages, covering 360 farmers of Atpadi and Jat block of Sangli district and Sangola and Mangalwedha block of Solapur district in western Maharashtra. Consumption is a significant activity performed by the households where in which drought significantly impacted its food consumption pattern by causing a change in the structure of food consumption baskets. The MPCE share on Jawar of small farmers (11.80%) was higher as compared to medium farmers (10.94%) and large farmers (9.74%). The share of monthly per capita consumption expenditure of milk (liquid) of large farmers (16.39%) was very high as compared to small farmers (12.41%) and medium farmers (13.07%). The monthly per capita expenditure of transport, communication & entertainment of large farmers (Rs.65) was high as compared to medium farmers (Rs.50) and small farmers (Rs.43). The monthly per capita expenditure on education of small farmers was Rs.100 (8.74%), medium farmers Rs.118 (9.35%) and the large farmers Rs.169 (11.13%). During the reference period in a study area. The average MPCE of large farmers were 1.33 times larger than the MPCE of small farmers.